Challenges in Correspondent Banking in the Small States of the Pacific - Alwazir, Jihad (IMF Working Papers; Working Paper ;, 2017)
Access to financial services in the small states of the Pacific is being eroded. Weaknesses in Anti-Money Laundering and Combating the Financing of Terrorism compliance in the context of high levels of remittances are contributing to banks' decisions to withdraw corresponding banking relationships and close bank accounts of money transfer operators. In this paper, we gather evidence on these developments in the small states of the Pacific, discuss the main drivers, and the potentially negative impact on the financial sector and macroeconomy. We then identify the collective efforts needed to address the consequences of withdrawal of corresponding banking relationships and outline policy measures to help the affected countries mitigate the impact.